Ocena aktywności mięśnia poprzecznego brzucha z wykorzystaniem urządzenia Pressure Bio-feedback Stabilizer u osób z dolegliwościami bólowymi kręgosłupa w odcinku lędźwiowo-krzyżowym = Assessment of transverse abdominal muscle activity with the use of Pressure Bio-Feedback Stabilizer among people with low back pain - Kochański, Bartosz; Fifielska, Beata; Kałużny, Krystian; Kałużna, Anna; Zukow, Walery; Hagner-Derengowska, Magdalena (Journal of Education, Health and Sport, 2016)
Kochański Bartosz, Fifielska Beata, Kałużny Krystian, Kałużna Anna, Zukow Walery, Hagner-Derengowska Magdalena. Ocena aktywności mięśnia poprzecznego brzucha z wykorzystaniem urządzenia Pressure Bio-feedback Stabilizer u osób z dolegliwościami bólowymi kręgosłupa w odcinku lędźwiowo-krzyżowym = Assessment of transverse abdominal muscle activity with the use of Pressure Bio-Feedback Stabilizer among people with low back pain. Journal of Education, Health and Sport. 2016;6(7):488-497. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.58739 http://ojs.ukw.edu.pl/index.php/johs/article/view/3712 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.06.2016. Revised 15.07.2016. Accepted: 26.07.2016. Ocena aktywności mięśnia poprzecznego brzucha z wykorzystaniem urządzenia Pressure Bio-feedback Stabilizer u osób z dolegliwościami bólowymi kręgosłupa w odcinku lędźwiowo-krzyżowym Assessment of transverse abdominal muscle activity with the use of Pressure Bio-Feedback Stabilizer among people with low back pain Bartosz Kochański1, Beata Fifielska2, Krystian Kałużny1, Anna Kałużna1, Walery Zukow3, Magdalena Hagner-Derengowska1,4 1 Katedra i Klinika Rehabilitacji, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu; 2 Bydgoska Szkoła Wyższa; 3 Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy; 4 Katedra Neuropsychologii, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu; Streszczenie Wstęp. Ważną rolę w stabilizacji kręgosłupa pełni mięsień poprzeczny brzucha. Doniesienia naukowe wykazują korelację między aktywnością tego mięśnia, a dolegliwościami bólowymi w odcinku lędźwiowo-krzyżowym. Cel pracy: 1. Ocena oraz porównanie aktywności mięśnia poprzecznego brzucha z wykorzystaniem urządzenia Pressure Bio-Feedback Stabilizer u osób z dolegliwościami bólowymi kręgosłupa w odcinku lędźwiowo-krzyżowym oraz u osób bez dolegliwości bólowych kręgosłupa w odcinku lędźwiowo-krzyżowym. 2. Ocena poziomu zgodności ocen dwóch terapeutów w badaniu aktywności mięśnia poprzecznego brzucha z wykorzystaniem urządzenia Pressure Bio-Feedback Stabilizer. Materiał i metody. Badania przeprowadzono na grupie 50 osób w wieku 28,36, w tym 28 kobiet oraz 22 mężczyzn. Badanych podzielono na dwie grupy: Grupę I - badaną stanowiły osoby z dolegliwościami bólowymi kręgosłupa w odcinku lędźwiowo – krzyżowym z aktualnym epizodem bólowym trwającym minimum 3 miesiące. Grupę II - kontrolną stanowiły osoby „zdrowe” bez dolegliwości bólowych w odcinku lędźwiowo – krzyżowym przez minimum 6 miesięcy. Wyniki. U osób z dolegliwościami bólowymi kręgosłupa obserwuje się nieprawidłową aktywację mięśnia poprzecznego brzucha. Analiza statystyczna wykazała istotne różnice pomiędzy badanymi grupami w aktywności mięśnia poprzecznego brzucha - p<0,05. Współczynnik zgodności ICC dla dwóch terapeutów badających aktywność mięśnia poprzecznego brzucha z wykorzystaniem urządzenia Pressure Bio-Feedback Stabilizer wynosi - 0,82. Wnioski: 1. U osób z dolegliwościami bólowymi kręgosłupa w odcinku lędźwiowo-krzyżowym obserwuje się nieprawidłowości w aktywności mięśnia poprzecznego brzucha. 2. Stopień zgodności ocen dwóch terapeutów badających aktywność mięśnia poprzecznego brzucha z wykorzystaniem urządzenia Pressure Bio-Feedback Stabilizer jest dobry. Abstract Introduction: Transverse abdominal muscle plays important role in spine stabilization, researches show a correlation between this muscle activity and physical pain and health ailments of low back. The aim of this thesis: 1.Assessment and comparison of Transverse abdominal muscle activity with the use of Pressure Bio-Feedback Stabilizer among people suffering from physical pain and health ailments of low back and among people who do not suffer from these ailments. 2. Description of level of consensus of two therapists’ assessment of Transverse abdominal muscle activity examination with the use of Pressure Bio-Feedback Stabilizer Materials and methods: The research was conducted among a group of 50 people age between 28,36, 28 women and 22 men. The examined were divided into two groups: group 1- 25 people (12 women and 13 men) and control group- 25 people (16 women and 9 men). Group 1 consist of people suffering from physical pain and health ailments of lower part of the spine who currently suffer for at least 3 months. Group 2 (control group) consist of people who do not suffer from physical paints and health ailments in the lower part of the spine for at least 6 months. Results: Incorrect transverse abdominal muscle activation was observed among people with physical pain and health ailments in the lower part of the spine. Statistical analysis showed significant differences between two examined groups in transverse abdominal muscle activity- p<0,05. Index of consistency ICC for two therapists examining transverse abdominal muscle activity with the use of Pressure Bio-Feedback Stabilizer equals 0.82. Conclusions: 1. Incorrect transverse abdominal muscle activity was observed among people with physical pain in the lumbar part of the spine. 2. Index of consistency of assessment for two therapist examining transverse abdominal muscle activity with the use of Pressure Bio-Feedback Stabilizer is good. Słowa kluczowe: urządzenia Pressure Bio-Feedback Stabilizer, dolegliwości bólowe kręgosłupa, kręgosłup lędźwiowo-krzyżowy, TrA. Key words: Pressure Bio-Feedback Stabilizer, low back pain, lower part of the spine, TrA.